KARAKTERISTIK RESERVOIR BATUAN KARBONAT FORMASI BATURAJA BERDASARKAN ANALISIS PETROFISIKA DI LAPANGAN ‘TI’ CEKUNGAN SUMATERA SELATAN - Soesanto, Edy; Handayani, Ani; DJamal, Dzikri Walisyah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Currently, oil and gas still play an important role as fuel in the industry. The 'TI' field is located in the Jambi Sub Basin, South Sumatra, which is one of the hydrocarbon-producing areas. The research area focuses on the Baturaja Formation. The processed data is in the form of wireline logs from 4 wells, core data and also mudlog data from TI-1 well. In the analysis of facies and depositional environments there are 3. In the subarcose interval in the off reef depositional environment on the open shelf. Furthermore, the second is foraminifera facies with limestone characteristics containing fine sand grains. This facies is found in the reef core depositional environment. Third, there is a coral mudstonedolostone facies with characteristics of few siltstones to fine sand grains found in the outer lagoonal depositional environment. Based on petrophysical calculations, the cut off value of Vsh is 40%, the cut off phie is 3%, and the cut off sw is 70%. From the results of the analysis and comparison of each well, it can be concluded that the TI-1 and TI-2 wells in the reef core depositional environment and also the outer lagoonal have the best quality with good hydrocarbon content. So that in the future further exploration and development can focus on these facies to increase the effectiveness of field development.